Efektifitas Penggunaan Abu Gosok Jerami dengan Abu Pelepah Kelapa pada Kualitas Telur Asin Ayam Broiler - Fajri, Siti Rabiatul; Armiani, Sucika; Masiah, Masiah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2021)
Broiler eggs are one of the eggs that have the highest consumption rate compared to other types of eggs. However, the shelf life of broiler eggs is very short. The purpose of the study was to analyze the effectiveness of using straw scrubbing ash with coconut fronds in the process of making salted eggs. The research was conducted by analyzing the organoleptic test results of respondents on the quality of broiler chicken salted eggs. The results of the study stated that the results of organoleptic tests using statistical tests at a significance level of 5%, in treatment P0 obtained an Fcount value of 8.954 which was greater than Ftable of 2.47, in P1 obtained an Fcount of 2.861 which was greater than Ftable of 2.47, and in P3 the Fcount value of 5.912 is greater than Ftable of 2.47. Meanwhile, in the P2 treatment, the Fcount value of 0.434 was smaller than the Ftable of 2.47. Thus, it can be concluded that the quality of salted eggs using straw rub ash with coconut fronds in the P0, P1, and P3 treatments was significantly accepted by the respondents. In addition, the quality of broiler chicken salted eggs in treatment P2 was not significantly different and was declared unacceptable by the respondents.